A dynamic GIS-based tool for truck volume estimation - Boilé, Maria; Golias, Mihalis (My University, 2004)
A geographic information systems (GIS)-based approach for estimating truck volumes and flows using classification counts and socio-economic data is now available. The add-on tool can assist transportation planners in obtaining truck volume, flow and percentage profiles on state roadways and visualizing predictive socio-economic data.